Caesarean delivery and risk of developing atopic diseases in children - Anak Agung Tri Yuliantini; Mohammad Juffrie; Ketut Dewi Kumara Wati (Indonesian Pediatric Society Publishing House, 2014)
Background Caesarean delivery has been suggested to alter neonatal immune respon ses and increase the risk of atopic diseases. Howevei; previous studies have reported inconsistent findings. Objective To investigate a possible association between caesarean delivery and the development of atopic diseases in children. Methods This case-control study involved 100 children aged 3 months-12 years, in Sanglah Hospital, Denpasai; Indonesia. Fifty infants and children with a confirmed diagnosis of atopic diseases and 50 sex-paired controls (non-atopic infants and children) were enrolled. Demographic data was obtained, including mode of delivery and relevant history connected to atopic diseases. Skin prick test to four common aeroallergens was performed in all subjects. Possible confounding factors were considered in a multivariable logis tic regression model. Results Caesarean section was not significant as a risk factor for atopic diseases in a multivariate analysis [OR 2.4 (95%CI 0.7 to 8.4; P=0.164)]. Howevei; multiple logistic regression analysis showed that atopic diseases was significantly associated with a positive family history of atopy. Furthermore, caesarean section was associated with a higher risk of atopic diseases in a subgroup analysis for family history of atopy [OR= 4 (95%CI 1 to 16.2; P= 0.04)]. Conclusion Children delivered by caesarean section and have a family history of atopy have a 4-fo ld higher risk of atopic diseases.